2021
DOI: 10.1016/j.nepr.2021.102988
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study of midwifery students’ experiences of COVID-19: Uncertainty and expendability

Abstract: The impact of COVID-19 on midwifery students is anticipated to be multi-faceted. Our aim was to explore Australian midwifery students’ experiences of providing maternity care during the COVID-19 pandemic. In a cross-sectional study 147 students were recruited through social media. Data were collected through an online survey and semi-structured interviews. Surveys were analysed using descriptive statistics; interviews and open text responses were interpreted through qualitative analysis. Findings revealed stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 32 publications
5
40
0
5
Order By: Relevance
“…Consistent with other qualitative studies on previous outbreaks, HPs faced numerous stressors, such as the fear of catching COVID-19 and spreading it to others; uncertainty about the virus, the disease, and the future; stigmatization, short-staffing, and inadequate PPE. 22 , 26 , 27 …”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Consistent with other qualitative studies on previous outbreaks, HPs faced numerous stressors, such as the fear of catching COVID-19 and spreading it to others; uncertainty about the virus, the disease, and the future; stigmatization, short-staffing, and inadequate PPE. 22 , 26 , 27 …”
Section: Discussionmentioning
confidence: 44%
“…Consistent with other qualitative studies on previous outbreaks, HPs faced numerous stressors, such as the fear of catching COVID-19 and spreading it to others; uncertainty about the virus, the disease, and the future; stigmatization, short-staffing, and inadequate PPE. 22,26,27 Across separate cohorts of HPs in 2020, the level of moral injury increased dramatically, and functional impairment from moral injury symptoms nearly doubled. 14 This qualitative study adds additional context to these numbers; the emotions reported-isolation, alienation, betrayalsignificantly overlapped with the symptoms of moral injury in military and veteran populations.…”
Section: Discussionmentioning
confidence: 99%
“…Our data collection instrument was a self-administered semi-structured questionnaire established after reviewing relevant literature. 6,12,[14][15][16][17] It involved three sections: socio-demographic characteristics (nine questions), COVID-19's negative impacts on clinical learning (twelve questions), and proposed compensation mechanisms for ending long-term COVID-19 negative impacts on clinical learning (four questions). English version questionnaire was used to collect data.…”
Section: Data Collection Instrument and Pre-testmentioning
confidence: 99%
“…Como apontado anteriormente, a necessidade de canal oficial é de suma importância para facilitar o aprendizado e conhecimento sobre como lidar em campo prático. Por isso, vale a pena que as universidades se juntem para proporcionar a esse discente, além de conhecimento teórico, mais conhecimento prático(Kuliukas et al, 2021).Kochuvilayil e colaboradores (2021) compararam conhecimento, ansiedade, preocupações acadêmicas e comportamentos preventivos entre estudantes de enfermagem na Austrália e na Índia, durante a pandemia COVID-19. Foram analisados 99 estudantes australianos e indianos.…”
unclassified